Wnt signaling loss accelerates the appearance of neuropathological hallmarks of Alzheimer's disease in J20-APP transgenic and wild-type mice - Tapia-Rojas, Cheril; Inestrosa, Nibaldo C. (My University, 2018)
Alzheimer's disease (AD) is a neurodegenerative pathology characterized by aggregates of amyloid-beta (A beta) and phosphorylated tau protein, synaptic dysfunction, and spatial memory impairment. The Wnt signaling pathway has several key functions in the adult brain and has been associated with AD, mainly as a neuroprotective factor against A beta toxicity and tau phosphorylation. However, dysfunction of Wnt/beta-catenin signaling might also play a role in the onset and development of the disease. J20 APPswInd transgenic (Tg) mouse model of AD was treated i.p. with various Wnt signaling inhibitors for 10 weeks during pre-symptomatic stages. Then, cognitive, biochemical and histochemical analyses were performed. Wnt signaling inhibitors induced severe changes in the hippocampus, including alterations in Wnt pathway components and loss of Wnt signaling function, severe cognitive deficits, increased tau phosphorylation and A beta(1-42) peptide levels, decreased A beta 42/A beta 40 ratio and A beta(1-42) concentration in the cerebral spinal fluid, and high levels of soluble A beta species and synaptotoxic oligomers in the hippocampus, together with changes in the amount and size of senile plaques. More important, we also observed severe alterations in treated wild-type (WT) mice, including behavioral impairment, tau phosphorylation, increased A beta(1-42) in the hippocampus, decreased A beta(1-42) in the cerebral spinal fluid, and hippocampal dysfunction. Wnt inhibition accelerated the development of the pathology in a Tg AD mouse model and contributed to the development of Alzheimer's-like changes in WT mice. These results indicate that Wnt signaling plays important roles in the structure and function of the adult hippocampus and suggest that inhibition of the Wnt signaling pathway is an important factor in the pathogenesis of AD.
Keywords: amyloid-beta; app; gsk3-beta; wnt signaling; wnt target genes; wnt/beta catenin